Antenatal Care Compliance within a Matrilineal Society: Husbands’ Knowledge and Attitudes among Urang Sumando in Padang Pariaman - Yesi Maifita; Tukimin bin Sansuwito; Santhana L. Panduragan (Journal of Health Science and Medical Therapy, 2026)
Husband involvement is a critical determinant of Antenatal Care (ANC) compliance. In Padang Pariaman Regency, this involvement is uniquely shaped by the matrilineal culture through the concept of Urang Sumando, in which husbands are positioned as “guests” within the wife’s family, often limiting their authority in maternal health decision-making. This study aimed to analyze the relationship between husbands’ knowledge and attitudes and maternal ANC compliance within this specific cultural context. A cross-sectional study was conducted between May and August 2025 involving 100 pairs of pregnant women and their husbands. Husbands’ knowledge and attitudes were assessed using validated questionnaires, while ANC compliance was verified through an audit of the Maternal and Child Health Book. Data were analyzed using chi-square tests and logistic regression. The results showed that ANC compliance reached 71%, with 58% of husbands demonstrating good knowledge and 62% showing positive attitudes toward ANC. Good knowledge was significantly associated with ANC compliance (OR = 3.21; 95% CI 1.30–7.93; p = 0.009), as was a positive attitude (OR = 2.74; 95% CI 1.16–6.49; p = 0.019). After controlling for age, education, and living status with in-laws, both knowledge (aOR = 2.70; 95% CI 1.12–6.52; p = 0.027) and attitude (aOR = 2.33; 95% CI 1.03–5.25; p = 0.042) remained significant predictors of compliance. Living with in-laws tended to reduce the likelihood of ANC compliance, although this association was not statistically significant (aOR = 0.52; 95% CI 0.24–1.13; p = 0.097). In conclusion, husbands’ knowledge and attitudes play a significant role in improving ANC compliance. Educational interventions grounded in local wisdom and involving both husbands and extended family members are strongly recommended.